Study on Climate Change and Disaster Related Loss and Damage Accounting - Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2023)
The 28th United Nations Conference of Parties (COP 28) in November 2023 started with the manifestation of concrete commitments from developed countries and ended with a progressive promise to complete the establishment of a climate change loss and damage fund, sustain and administer country contributions, and continue to work toward fossil fuel reduction and disaster risk reduction and management. The move contributes toward an equitable burden distribution between the highest GHG emitters in the global community and the most affected nations by climate-related disasters. This is important as evidences show that developing countries like the Philippines are disproportionately more affected by climate change-related disaster events. This study assessed the particulars of the climate and disaster related loss and damage accounting in the Philippines and looked into ways to better the country's position to tap the newly establish Loss and Damage Fund.
Keywords: 330; climate change impact; loss and damage accounting; disaster risk reduction and management